Globalsoilmap - digital soil mapping from country to globe : proceedings of the Global Soil Map 2017 Conference, July 4-6, 2017, Moscow, Russia /: proceedings of the Global Soil Map 2017 Conference, July 4-6, 2017, Moscow, Russia. (2017) - Unknown
No abstract available